Risk factors in international rail-system projects - Ali Telmaç; Gözde Tantekin-Çelik (Advances in Civil and Architectural Engineering)
Construction projects carry many risks due to their long-term, changeable, and dynamic structures. When these risks are transferred to the international environment, they may give rise to new risks and increase the effects of existing risks. International railway-system projects, involve many project-specific risks due to their long duration and high volume of technological manufacturing. Opening completed rail lines for use requires the anticipation of risks that may arise during the warranty period. This study conducted a survey with construction-sector employees working on rail-system projects in Turkey, Italy, and India regarding the risks they face within the scope of the project. Based on the exploratory factor analysis, the risks encountered in international rail-system projects were grouped under three factors: "management-related risks,” "time- and cost-related risks,” and "product quality-related risks.” The results showed that time and cost risks differed by country.